Strategi Pemasaran UMKM Roti Al Batsit Kota Bengkulu - Susena, Karona Cahya; Herlika, Eren herlika; Roziana, Refsi; Efendi, Fithria Habib (Universitas Dehasen Bengkulu, 2024)
Roti Al Batsit MSME is a small business engaged in the food industry located in Bengkulu City. As one of the MSMEs, the challenge that must be faced is how to increase product sales and introduce the Roti Al Batsit brand to the public. Therefore, a community service programme entitled